Pengayaan Kompos Tandan Kosong Kelapa Sawit (Tkks) Dengan Spent Earth Terhadap Pertumbuhan dan Hasil Tanaman Kedelai (glycine max (l.)Merril) di Lahan Gambut - Adwa, Tengku Yulia Ispi; ', Nelvia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to study the effect composting of oil palm empty fruit bunches enriched spent earth to the growth and yield of soybean. This research conducted on peat soil at Kualu Nenas village, Tambang sub-district, Kampar Regency starts from March to June 2013. The material used was soybean variety Grobogan, empty fruit bunches of oil palm (EFBOP) compost and spent earth (spent earth is a byproduct of vegetable oil processing). Research carried out experimentally using complete randomized design (CRD) which consists of five treatmentsKS0, KSI, KS2, KS3 and KS4(K = 5tonsEFBOPcompost/ha, S0,1,2,3 and 4= 0; 0,5; 1; 1,5’ and 2 tons spent earth/ha) and four replications.The parameters observed are plant height, flowering date, harvesting age, number of pods of pithy, the percentage number of pithy, seed pods per pods, seed weight andweight of 100 seeds. The result show that 5 tons/ha of EFBOP compost with spent earth 0-2 tons/ha doesn’t have significant influence on plant's growth, but soybean seed weight tended to increase the provision of 5 tonsempty fruit bunches of oil palm compost /ha enriched1,5 tonsspent earth/ha. Keywords : Empty fruit bunches of oil palm (EFBOP) compost, spent earthand Soybean